2001
DOI: 10.1123/apaq.18.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Adults with Mental Retardation in a Video- and Leader-Directed Aerobic Dance Program

Abstract: The purpose was to compare two conditions (leader-plus-video, video-only) that involved different levels of support on facilitating engagement in moderate to vigorous physical activity (MVPA) in adults with mental retardation (MR). Engagement was examined during 10-min aerobic dance sessions conducted 3 days per week over a 10-week experimental period followed by a 4-week maintenance period. The experimental design was single subject reversal (B-A-B-A). Participants were 17 adults (mean age = 42.6 years) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…The modicum of evidence that does exist demonstrates that short-and medium-term improvements in physical activity levels are possible. The evidence to date demonstrates that a targeted intervention in the workplace can improve physical activity levels in that discrete context, 18 but to achieve a more pervasive increase in physical activity among adults with intellectual disabilities a 'multipronged' and sustained approach is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modicum of evidence that does exist demonstrates that short-and medium-term improvements in physical activity levels are possible. The evidence to date demonstrates that a targeted intervention in the workplace can improve physical activity levels in that discrete context, 18 but to achieve a more pervasive increase in physical activity among adults with intellectual disabilities a 'multipronged' and sustained approach is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, the worksite intervention by Stanish and colleagues 18 was designed to increase physical activity while at work. The only study delivered in people's homes was the Swedish study by Bergström and others.…”
Section: Mcdermott and Colleaguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Draheim et al [2002cDraheim et al [ , 2003 and Stanish and Draheim [2005] indicated low to moderate intensity activities where highly reported. The preference of lower intensity activities is supported by the high participation in optional, lower intensity (moderate) physical activity programs by adults with MR [Stanish et al, 2001]. Stanish and Draheim [2005] concluded that adults with MR may find less intense activities more enjoyable compared to activities that require a high level of physical stamina.…”
Section: Behavioral Risk Factorsmentioning
confidence: 99%
“…Adults with ID may find less intense activities more enjoyable compared to activities that require a high level of physical stamina (Stanish and Draheim 2005). Hence, in this population low-to-moderate intensity activities are often reported (Draheim et al 2003;Stanish and Draheim 2005) and rates of optional participation in low-to-moderate physical activity programs are high (Stanish et al 2001). In any case, exercises implemented should be enjoyable and should include motivational strategies to ensure long-term participation.…”
Section: Importance Of Physical Activity Interventionsmentioning
confidence: 98%